Efektivitas Pendidikan Agama Islam Berbasis Kemampuan Otak dalam Meningkatkan Motivasi dan Hasil Belajar Siswa - sodikin sodikin (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2017)
In the era of globalization that carries the positive and negative impacts, especially in the various lines of life and education, quality assurance develops so fast in moving educational institutions. There is a need for good quality educators to improve public trust in the progress of the learning service. Therefore, educators must have excellent planning to face a great challenges. One of the efforts that must be done by educator is the ability to provide the service of learning that can open all the exist possibilities in their minds to make students becomes a strong and intelligent man in science and have a good morals. Results of this study indicate that brain-based learning is effective for increasing motivation and students learning outcome at madrasah level, so that the student’s learning needs are met to be able to develop their abilities.